THE THEME OF SURVIVAL IN ISAAC ASIMOV’S “MAROONED OFF VESTA” - Akhmedov , Rafael (Zamonaviy filologiya muammolari, 2025)
Abstract. The article focuses on both narrative and thematic analysis, regarding the story “Marooned off Vesta” (1939) by Isaac Asimov as one that presents a vivid exploration of human perseverance, rational thinking, and adaptive strategies in an extraterrestrial environment. The narrative already anticipates Asimov’s recurring themes, where logical reasoning, cooperation, and scientific knowledge appear as key tools in confronting existential threats. Close textual analysis, supported by literary context and references to research papers, allows to explore the relationship between narrative structure, character development, and scientific plausibility in presenting survival both as a physical need and as a philosophical idea. The story is placed within the wider tradition of interwar and pre-war space-survival narratives, considering its educational role and ideological meaning in the 21st-century science fiction.